La importancia de la participación de los padres en la enseñanza del inglés en Educación Infantil - Pino Juste, Margarita; Rodríguez López, Beatriz (Didáctica. Lengua y Literatura, 2007)
In this article we try to approach the different ways the parents can participate in the school. Specifically, we will focus on their participation in the English class at the rural schools of the Baixo Miño. We understand by participation a process of learning, literacy, and, at the same time, an effective instrument for the constant training and education of human beings. In order to do this we will use a descriptive methodology and instruments like observation, video recording, the English teachers’ life histories, interviews to the school headmasters and questionnaires to the parents and tutor teachers, as well as the content analysis of the school official documents. Despite both parents and teachers attach great importance to the participation, the truth is that it is basically focused on the collaboration in isolated activities. The reasons are varied, we emphasize two: the misgiving of the teacher about the parents controlling their work and the parents ignorance about the different ways of participation. Le but de ce travail est de connaître les différentes façons de participation des parents à l'école. En particulier, on se concentre sur la participation des parents aux classes d’anglais (à l’école maternelle) qui se développe dans les écoles rurales regroupées du Département du «Baixo Miño». On comprend la participation comme un processus d'apprentissage, d'alphabétisation et, en meme temps, un instrument efficace pour la formation et l'éducation permanente des personnes. On emploie une méthodologie descriptive et on utilise des instruments comme l'observation, les enregistrements vidéo, les interviews aux professeurs et aux directeurs des écoles et des questionnaires aux parents, ainsi que l'analyse de contenu des documents officiels de l’établissement. Malgré le fait que les parents et les professeurs accordent une grande importance à la participation, en vérité, celle-ci ne touche qu’à la collaboration dans des activités ponctuelles. Les raisons de ce fait sont nombreuses, mais nous soulignons simplement deux: la méfiance du professorat à l’égard du contrôle des parents sur leur travail et l'ignorance des parents des différentes façons de participation.